IMPLEMENTASI E-CATALOGUE TERHADAP EFISIENSI PEMBELANJAAN PADA PENGADAAN BARANG/JASA BADAN PENDAPATAN DAERAH (BAPENDA) KOTA MEDAN - Hutabarat, Siti Lutfia; Nasution, Annio Indah Lestari (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
This research aims to determine the impact of implementing the E-Catalog system on spending efficiency in the goods/services procurement process at the Medan City Regional Revenue Agency (BAPENDA). E-Catalogue is an electronic information system that contains lists, types, technical specifications and prices of various goods/services from various providers to facilitate electronic transactions. The research method used is a case study with a qualitative approach. Data was collected through in-depth interviews with Medan City BAPENDA employees who were involved in the goods/services procurement process. In addition, a review of documents related to the implementation of e-Catalog at BAPENDA was carried out. The research results show that the implementation of E-Catalog has increased shopping efficiency in BAPENDA Medan City. This system is able to speed up the procurement process, reduce costs, guarantee reasonable prices and quality, and facilitate user access. Apart from that, E-Catalogue also increases transparency and accountability in managing the goods/services procurement budget.